Analysis of Value Added Distribution of Brown Sugar (Saka) Agroindustry in Bukik Batabuah Village Canduang Sub-district Agam Regency - Firnalista, Nadia; Nofialdi, Nofialdi; Azriani, Zednita (Indonesian Journal of Agricultural Research, 2018)
Rural agroindustry can absorb a relatively high labor rate, but the added value of the products is very low, resulting in low labor productivity. This research aims at describing the process of sugarcane into brown sugar and analyzing the added value of brown sugar agroindustry as well as its distribution in Bukik Batabuah Village, Canduang Agam Sub-district. The data were collected from six brown sugar processing home industries. This research found that there were three kinds of brown sugar namely saka kariang, saka gatah kuniang and saka gatah merah, which were only different in the time of cooking, storage process of tengguli, and heating of tengguli on saka gatah processing. These made the three types of brown sugar have different texture, taste, color and price. From their added value, saka kariang and saka gatah kuniang were classified as medium products, while saka gatah merah was classified as a low product. In addition, this research reveals that the smallest added value distribution was received by paid labors. Based on the findings, the following suggestions are recommended: (1) the brown sugar business should focus on developing a business of saka kariang processing; and (2) the added value of brown sugar could be enhanced by the use of effective and efficient production machinery, so that the added value distributed to the brown sugar agroindustry could be improved